Bee Floral Calendar of Wild and Cultivated Plants in Pyuthan District, Nepal - Subedee, Surakshya; Thapa, Resham Bahadur; Shrestha, Tirtha Kumar (Journal of Agriculture and Forestry University, 2025)
The availability of floral sources and their flowering duration are crucial for beekeeping, honey production, and crop pollination. This study was conducted to develop a floral calendar for beekeeping, exploring the potential of wild and cultivated bee flora in Pyuthan district. Primary data were collected from direct observation, 20 key informant surveys, and 9 focus group discussions in each municipality involving 227 beekeepers. In this study, a total of 100 plant species from 44 different families were identified and further categorized into nectar (N), Pollen (P), and both nectar and pollen source (NP). The honey flow period was reported to be from March to June and October to November, with the highest number of flowering plants (49) in April. While the winter season (December- February) was identified as a dearth period each having 10 flowering plants. Among the identified plant species, wild plants were found to be the major bee flora with 19 N1P1 plants, followed by fruits with 9 plant species. Based on the floral calendar analysis, the bee flora of the dearth period can be multiplied, and conservation of wild plants can be done to ensure year-round foraging of the honeybee and to minimize foraging disputes among farmers.